Il testimone necessario. Memoria della shoah e costruzioni identitarie - Giovanni Leghissa (Rivista di Estetica, 2010)
The article discusses three issues that are strictly interwoven with each other. The first is the relation between the eyewitnesses’ memories of past events, the recording of such memories in institutionalized archives, and the historical reconstructions thereof. The issue is treated within a systematic perspective, in order to clarify in which sense eyewitnesses constitute the basic pillars of any historical work.The second is the role played by eyewitness of the Shoah, which is related to the “politics of memory”. The social function of such a politics is important not as a form of monumentalization of the past, but rather as an attempt to improve a shared memory for an event – the Shoah - whose cultural and political meaning concerns the European heritage as a whole and not only the history of the Jewish people.The third is an attempt to read the Shoah as an expression of biopolitics - in the foucauldian sense of the term. That will provide a framework for a discussion about contemporary forms of social and institutionalized violence, under the assumption that the scope of the Holocaust Studies and their methodology reach far beyond the phenomena related to the Shoah.